Changes in wettability of wood surface using electron beam irradiation. Issue 4 (3rd July 2020) - Huber, H.; Haas, R.; Petutschnigg, A.; Grüll, G.; Schnabel, T.
ABSTRACT: This study deals with the influence of electron beam irradiation (EBI) on the wettability of Norway spruce surface samples. To evaluate this possible effect in detail, the changes in chemistry and wood structure were analysed using the methods of IR spectroscopy and Scanning Electron Microscopy (SEM). The surface wettability was determined by the contact angle measurement method. The results of infrared spectra show decreased relative numbers of available hydrophilic groups (e.g. hydroxyl and carbonyl groups) in the wood surfaces due to the electron beam irradiation. This behaviour is consistent with the values from the surface wettability measurements. Structural differences of the wood surfaces after electron beam irradiation were not detectable. Based on these findings pre-treatment of wood surfaces for industrial usages can be a potential field of application of this technology.